The development of a PDA-based communication architecture for surveillance services. (4th August 2005) - Li, Sheng-Tun; Shue, Li-Yen; Hsieh, Huang-Chih
We present a real-time client–server communication architecture for surveillance services with personal digital assistants (PDAs), and propose an application-layer communication protocol for enhancing its performance. The architecture is based on pure Java technology. With it, PDAs will be able to issue commands, carry out various functions, and receive feedback through the server. A successful application of a remote surveillance system is developed, which allows PDA with both Palm OS and Windows CE to capture snapshots of the monitoring scene, and directs other communication activities, like calling pager, faxing images, or sending instant messages to cellular phones.